Pediatric High-grade Meningioma: A Case Report - Nagi A. Massoud; Abdulrahman H. Alashkar (Dr. Sulaiman Al Habib Medical Journal)
The development of meningiomas in the pediatric population is rare. Moreover, meningiomas are biologically and genetically distinct from their adult-onset counterparts, and more research on this topic is emerging. Nevertheless, no guidelines have been specifically tailored for the management of pediatric meningiomas. Here, we present the case of a 15-year-old female patient who presented with involuntary movements of her right upper limb. A gadolinium-enhanced brain magnetic resonance imaging subsequently revealed a left parasagittal frontoparietal mass lesion. She underwent craniotomy and surgical resection of the mass lesion, and histopathological examination confirmed a high-grade meningioma. The patient was referred to a higher oncology center for further evaluation and adjunct radiotherapy as needed. Research on pediatric meningiomas remains limited, and further studies are required to develop management guidelines that reflect their clinically and biologically distinct nature.